Clinical Response and Complications are not Associated with Drug Levels in Patients with Severe Ulcerative Colitis on IV Cyclosporine Induction Therapy. Issue 6 (1st March 2018) - Patel, Parita; Yarur, Andres; Dalal, Sushila; Sakuraba, Atsuhi; Rubin, David T; Hanauer, Stephen B; Hanan, Ira; Raffals, Laura H; Cohen, Russell D; Pekow, Joel
Abstract: Background: IV ciclosporin therapy is effective in steroid-refractory ulcerative colitis. The optimal drug level to achieve response and minimize complications during induction therapy is not known. Aim: The primary aim was to evaluate if serum ciclosporin drug levels are associated with increased risk of colectomy within 90 days of hospitalization. Secondary aims were to determine if ciclosporin levels are associated with avoidance of colectomy at 7 and 30 days, if ciclosporin levels are associated with drug-related and postoperative complications, and if patient-specific factors are associated with response to ciclosporin. Methods: We conducted a retrospective analysis of 81 hospitalized patients with steroid-refractory ulcerative colitis treated with ciclosporin. Risk factors for colectomy within 7, 30, and 90 days, medication-specific and postoperative complications were compared by first, mean, and peak ciclosporin level during IV induction therapy. Results: There were 47 patients (58%) who underwent surgery. There were no differences between initial, mean, and peak ciclosporin levels among responders and nonresponders and treatment-related or postoperative complications. Responders within 90 days had lower C-reactive-protein levels (20mg/L vs. 38mg/L, P = 0.01), lower serum albumin concentrations (3.4g/dL vs. 3.7g/dL, P = 0.03), and higher rates of kidney injury (50% vs 17%, P = 0.002). Conclusion: Initial, mean, and peak serum levels of ciclosporin did not correlate with response or toxicity. However, C-reactive-protein levels levels and kidney injury may be helpful in predicting clinical response to ciclosporin.